High compassion predicts fewer sleep difficulties: A general population study with an 11‐year follow‐up - Iina Tolonen; Aino Saarinen; Sampsa Puttonen; Mika Kähönen; Mirka Hintsanen (Brain and Behavior, 2023)
Abstract Introduction This study investigated the cross‐sectional and longitudinal associations between self‐reported compassion and sleep quality. Methods The data came from the population‐based Young Finns Study with an 11‐year follow‐up on compassion and sleep (n = 1064). We used regression models, multilevel models, and cross‐lagged panel models to analyze the data. Results The results showed that high compassion was cross‐sectionally associated with lesser sleep deficiency and fewer sleep difficulties. High compassion also predicted fewer sleep difficulties over an 11‐year follow‐up (adjusted for age, gender, socioeconomic position in childhood and adulthood, body mass index, health behaviors, and working conditions). This association disappeared when controlling for depressive symptoms. The predictive pathway seemed to proceed more likely from high compassion to fewer sleep difficulties than vice versa. Discussion Compassion may buffer against sleep difficulties, possibly via reducing depressive symptoms.